Pemberian Terapi Jus Buah Bit untuk Meningkatkan Kadar Hemoglobin melalui Pendekatan Asuhan Keperawatan Keluarga pada Remaja Putri Penderita Anemia di Kecamatan Kemiling Kota Bandar Lampung - Juliawan , Ladin; Trismiyana, Eka; Setiawati (Jurnal Keperawatan Muhammadiyah, 2025)
Background: Anemia is defined as a condition in which blood hemoglobin levels fall below normal values. Adolescent girls are more susceptible due to monthly iron loss during menstruation. Beetroot juice has been identified as an effective non-pharmacological intervention, as it contains essential nutrients that support erythropoiesis and are rapidly absorbed by the body. In liquid form, beetroot is absorbed by the digestive system within approximately 20 minutes, compared to around 18 hours for whole fruit. Objective: The effectiveness of beetroot juice in increasing hemoglobin levels among adolescent girls with anemia was demonstrated through a family nursing care approach in Kemiling District, Bandar Lampung City. Method: This study employed a quantitative method with a one-group pre-test and post-test design. The sample consisted of two respondents selected through purposive sampling. The intervention was conducted over a period of seven days involving two subjects, An. H and An. T. Results: The evaluation of the seven-day beetroot juice intervention showed an increase in hemoglobin levels in both subjects. In An. H, hemoglobin increased from 9.5 g/dL to 11.6 g/dL (a rise of 2.1 g/dL), while in An. T, it increased from 9.9 g/dL to 11.8 g/dL (a rise of 1.9 g/dL). Conclusion: Based on the results, it can be concluded that beetroot juice has a positive effect on increasing hemoglobin levels in adolescent girls with anemia. This study is expected to serve as a reference for the use of beetroot juice as an effective non-pharmacological therapy for managing anemia in adolescents.